Bogor Regency Government’s Strategy to Optimizing Public Procurement for Micro and Small Enterprises (MSE) Through E-Katalog - Niken Novia Sitaresmi; Lukman M Baga; Dwi Rachmina (Universitas KH. Abdul Chalim Mojokerto, 2025)
Technological advancements have had a significant impact across various sectors, including public procurement. The rise of e-marketplaces has been adopted by the government through the optimization of the electronic catalog (e-catalog) system. The e-catalog represents a governmental initiative aimed at promoting the involvement of micro and small enterprises (MSEs) in public procurement, thereby supporting regional economic development. This study employed a qualitative descriptive approach. The findings reveal that the implementation of the e-catalog policy for MSEs in Bogor Regency has not been fully effective. This suboptimal implementation is attributed to several factors, including inadequate procurement planning, the limited capacity of MSEs to execute projects, and hesitation among Procurement Officers (PP) and Commitment-Making Officials (PPK) in selecting available MSE providers.